2016
DOI: 10.1093/cid/ciw495
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Profiles and APOE4 Allele Impact Midlife Cognitive Decline in HIV-Infected Men on Antiretroviral Therapy

Abstract: Elevated cholesterol and APOE ε4 genotype were independent risk factors for cognitive decline in antiretroviral therapy–adherent human immunodeficiency virus (HIV)-infected men aged 50–65 years, whereas higher high-density lipoprotein attenuated cognitive decline. Treatment of dyslipidemia may reduce midlife cognitive decline among HIV-infected individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 39 publications
2
28
0
Order By: Relevance
“…In a combined multivariable analysis of the entire cohort, we found that higher HDL was associated with lower odds of cognitive impairment, which parallels results from studies in the general population [38,39]. Contrary to our results, however, time-varying higher HDL attenuated the rate of cognitive decline in men living with HIV from the Multicenter AIDS Cohort Study [40].…”
Section: Discussionsupporting
confidence: 70%
“…In a combined multivariable analysis of the entire cohort, we found that higher HDL was associated with lower odds of cognitive impairment, which parallels results from studies in the general population [38,39]. Contrary to our results, however, time-varying higher HDL attenuated the rate of cognitive decline in men living with HIV from the Multicenter AIDS Cohort Study [40].…”
Section: Discussionsupporting
confidence: 70%
“…The results of this study need to be interpreted in the light of several limitations. The results of several investigations into the genetic contributions to HAND suggest that the harmful effects of ApoE ε4 on cognitive function may be likely to be expressed at a later age (Valcour et al 2004;Pomara et al 2008;Panos et al 2013;Mukerji et al 2016;López et al 2017). Such a temporally mediated effect could explain some of the divergent literature findings regarding the role of ApoE in HAND.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, ApoE may play a role in some of the pathophysiological mechanisms underlying the deleterious consequences of HIV in the brain (Corder et al 1998). Studies that have investigated the link between genetic variation in ApoE and HAND have found evidence both for (Dunlop et al 1997;Corder et al 1998;Spector et al 2010;Andres et al 2011;Hoare et al 2013;Mukerji et al 2016;Wendelken et al 2016) and against (Dunlop et al 1997;Burt et al 2008;Pemberton et al 2008;Pomara et al 2008;Sun et al 2010;Joska et al 2010;Morgan et al 2013;Becker et al 2015) its involvement in HAND. These contradictory findings may in part be due to the failure to assess the interaction of ApoE with other risk factors (Cooley et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The APOEε4 genotype is a risk factor for elevated cholesterol in ART-adherent HIV(+) men aged >50 years [72] with a risk for a higher cognitive decline associated and cardiovascular problems.…”
Section: Hiv-1 and Risks Of Alzheimer's Disease (Ad) Pathogenesismentioning
confidence: 99%